Profiling of Single Garlic Extract Microencapsulation: Characterization, Antioxidant Activity, and Release Kinetic - Lestari, Sri Rahayu; Ghofur, Abdul; Maslikah, Siti Imroatul; Sunaryono, Sunaryono; Rahma, Amalia Nur; Aisyah, Dahniar Nur; Mufidah, Ikfi Nihayatul; Rifqi, Nadiya Dini; Prastita, Nenes; Miasih, Dewi Sekar; Baroroh, Alif Rosyidah El (Universitas Gadjah Mada, 2023)
Single garlic is known to have many benefits as an alternative therapy for various types of metabolic syndrome. The bioactive compounds, allicin and alliin, in garlic are unstable and easily degraded in digestion. Chitosan-alginate microencapsulation is thought to increase stability and protect active compound so its therapeutic effect is more optimal. This study aimed to characterize the microencapsulation chitosan-alginate of single garlic extract (MCA- SGE), as well as to examine the antioxidant activity and kinetic release of MCA-SGE in vitro. The research procedure includes the steps of single garlic extraction, preparation of MCA-SGE, characterization of MCA-SGE (PSA, SEM, and FTIR) as well as biological testing of MCA-SGE through antioxidant activity and kinetic release tests. PSA results showed the mean particle size of MCA-SGE was 439.0 ± 1.9 nm or 0.4 m with a polydispersity index (PDI) value of 0.579 ± 0.046 and a zeta potential value of 15.4 ± 0.3 mV. The SEM results showed that the morphology of MCA-SGE was spherical with a smooth surface and a micrometre size of 0.4 - 0.7 µm. The FTIR results describe a shift in absorption and addition of SGE functional groups after encapsulation. The results of the antioxidant activity test showed the antioxidant activity of MCA-SGE was 65%, while SGE was 55%. The results of the kinetic release showed that more allicin and alliin were released by SGE than MCA-SGE during the 4-hour kinetic release simulation. MCA-SGE has the potential to be used as a drug delivery system with controlled release.